Cat's claw [large type] - Albert, Susan Wittig (Albert, Susan Wittig. China Bayles mysteries., 2012)
Police Chief Sheila Dawson believes the death of Pecan Spring's computer guru, Larry Kirk, to be a suicide, perhaps triggered by his painful divorce. Further investigation reveals that Kirk's death wasn't self-inflicted. And the truth is reinforced by her friend China Bayles' news-Larry recently asked her for legal advice in regards to a stalker. As a police chief in a male-dominated force, Sheila meets many challenges, especially when her theories rock the boat in high profile cases like that of George Timms. He was caught breaking into Larry's computer shop to steal his own computer back because of dangerous personal information it contained. Now that Larry is dead, she's sure it's connected to the burglary. And she's also sure she'll get plenty of resistance on her assessment...Timms's time to turn himself in to the police comes and goes, and he's nowhere to be found. In her investigation, Sheila uncovers secrets, terrible secrets that would drive anyone to kill. So who then? It's up to Sheila to prove she's got what it takes to hunt down the predator that's loose on the streets of Pecan Springs...